Green Revolution in Parsa: Opportunities and Threats - Dube, Shiva Kant (Academic Voices: A Multidisciplinary Journal, 2014)
This article has attempted to focus upon the concept, historical development, process and impact of green revolution at global context. It has also incorporated to emphasize the adverse impact resulted by green revolution. The widespread acceptance of High Yielding Variety Seeds (HYVs) and extensive adaptation of dwarf and semi-dwarf plants of short cropping period has intensified the production and productivity of agricultural crops. But, excessive and uncontrolled use of chemical fertilizers and pesticides, insufficient irrigation and small land holdings has diminished and impoverished the soil fertility leading to desertification. This study has also overviewed the scenario of agricultural production and productivity of crops in Parsa district of Nepal being a developing country after the diffusion and acceptance of green revolution. This study would attract the attentions of planners, policy makers, stakeholders and farmers towards entertaining the impact of green revolution and make them aware about the threat created by it now and in the coming future in Nepalese context. Academic Voices, Vol. 3, No. 1, 2013, Pages 54-61 DOI: http://dx.doi.org/10.3126/av.v3i1.9989